TAS AKADIR, Tas Anyaman Bernahan Dasar Akar Keladi Air - Hidayat, Sy. Dian; A.W, Wahdini; Borneo, Alpian (Program Kreativitas Mahasiswa - Kewirausahaan, 2014)
Water taro root plants are wild plants mostly found abundantly in swamp area in the middle of the jungle and along the Kapuas river bank. Taro root plants are like creeping roots on trees with the roots dangling down along the tree height, with an estimate length 3 up to 7 metres. The shapes of these plants resemble stem nut, and if the inside part of taro root plants are pared, there is strong root of taro root plants to bind off. At a glance, the plants look like processed rattan, but taro root plants are much better due to their smooth and strong texture of the roots which makes the plants easy to be plaited into various handicraft. These plants are suitable as raw materials for webbing. For webbing handicraft, taro root plants are the typical commodity from West Kalimantan especially because of the raw matarials of these plants can only be found in Pontianak, West Kalimantan. Having seen a huge market opportunity in Pontianak, this business in promosing. Akadir Bag handmade product with the best servise and a good quality of raw materials can give satisfaction to the consumers. This is the main goal of promoting this product and introduce it as unique bag, and interesting webbing with taro root plants-the typical plant from West Kalimantan as the raw materials to the society.. This activity is conducted by the university students to encourage their spirit of creation, art, creativity, and enterpreneurship who are capable to see the market opportunity for the sake of gaining profits.Keywords : Water taro root webbing, West Kalimantan typical handicraft, Akadir Bag.